CULTURAL CREATIVE AR GAME AND SIDE EFFECTS EVALUATION - Ren Hsu, Der (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
In cultural creative industry, mobile games are one of the most increasing markets. Pokemon Go, as an Augmented reality (AR) in mobile games, may lead to both video game and physical activity, but it also inevitably triggers a certain degree of side effects. Unfortunately, there is little objective, scientific research focused on evaluating the risks of side effects that result from information exchange among mobile devices. In this study, the Grey Relational Analysis (GRA) is employed to identify and evaluate the risks of Pokemon Go. This research finds Walking or car accident, Disturbing sacred location, and Trespassing are the top three side effects. Cultural creative game is a new inevitable business trend, it is an unavoidable responsibility to our society to govern and constitute a legal environment for those AR game players.